2006
DOI: 10.1037/0022-0663.98.1.63
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a language and literacy intervention on Head Start children and teachers.

Abstract: A language and literacy intervention was implemented in 10 Head Start classrooms. Teachers were trained in specific book reading and conversation strategies. The focus of the intervention was to train teachers how to increase opportunities for language and vocabulary development in young children. At the end of the year, children in the intervention classrooms performed significantly better than children in the control classrooms on the Peabody Picture Vocabulary Test-III and the Expressive One-Word Vocabulary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
382
2
28

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 552 publications
(426 citation statements)
references
References 33 publications
14
382
2
28
Order By: Relevance
“…It may be that attendance in such workshops increased teachers' use of quality language modeling techniques, but it may also be true that teachers who exhibit high-quality instruction and who are good teachers of language are especially drawn to such workshops. Research provides some guidance concerning what high-quality professional development in the area of language instruction looks like (e.g., Girolametto, Weitzman, & Greenberg, 2003;Wasik et al, 2006), but we have insufficient detail on the workshop experiences of the teachers to draw any firm conclusions regarding this finding. When attempting to predict quality literacy instruction, results showed that teachers who reported a higher sense of self efficacy and held more adult-centered ideas received higher ratings for quality of literacy instruction.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…It may be that attendance in such workshops increased teachers' use of quality language modeling techniques, but it may also be true that teachers who exhibit high-quality instruction and who are good teachers of language are especially drawn to such workshops. Research provides some guidance concerning what high-quality professional development in the area of language instruction looks like (e.g., Girolametto, Weitzman, & Greenberg, 2003;Wasik et al, 2006), but we have insufficient detail on the workshop experiences of the teachers to draw any firm conclusions regarding this finding. When attempting to predict quality literacy instruction, results showed that teachers who reported a higher sense of self efficacy and held more adult-centered ideas received higher ratings for quality of literacy instruction.…”
mentioning
confidence: 84%
“…In these interventions, preschool educators are trained to utilize specific language-facilitation techniques in their formal and informal interactions with children to provide frequent exemplars of language forms and functions that are slightly advanced of (and thus responsive to) children's linguistic abilities. and meal time (e.g., Bunce, 1995;Dickinson, 2006;Girolametto & Weitzman, 2002;Huttenlocher, Vasilyeva, Cymerman, & Levine, 2002;McKeown & Beck, 2006;Wasik et al, 2006), and have been causally associated with accelerated language outcomes in preschool children.The defining characteristics of high-quality literacy instruction in the preschool classroom must be differentiated from the responsive and conversationally-oriented features of highquality language instruction. High-quality literacy instruction features systematic and explicit direct instruction that teaches children about the code-based characteristics of written language, to include both phonological and print structures.…”
mentioning
confidence: 99%
See 3 more Smart Citations